2015
DOI: 10.5194/acp-15-13507-2015
|View full text |Cite
|
Sign up to set email alerts
|

Global temperature response to the major volcanic eruptions in multiple reanalysis data sets

Abstract: Abstract. The global temperature responses to the eruptions of Mount Agung in 1963, El Chichón in 1982, and Mount Pinatubo in 1991 are investigated using nine currently available reanalysis data sets (JRA-55, MERRA, ERA-Interim, NCEP-CFSR, JRA-25, ERA-40, NCEP-1, NCEP-2, and 20CR). Multiple linear regression is applied to the zonal and monthly mean time series of temperature for two periods, 1979-2009 (for eight reanalysis data sets) and 1958-2001 (for four reanalysis data sets), by considering explanatory fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 35 publications
1
76
0
Order By: Relevance
“…We also assessed volcanic direct radiative impact by using volcanic index (calculated using clear‐sky net shortwave radiative flux at surface averaged over the selected domain) and introduced it as a predictor in multiple regression analysis; however, it gave similar qualitative responses (not shown) as is calculated using residual approach. The volcanic residual signal estimated here might contain some contributions (Fujiwara et al, ) from other random variations that are not included in the multiple regression; however, these contributions are much smaller compared to volcanic direct radiative and posteruption ENSO impacts, especially in the summer season (Dogar, Stenchikov, et al, ). Both the model and observation display cooling and drying anomaly over the entire MEA and South Asian regions except over the tropical belt that displays warming and drying anomaly.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We also assessed volcanic direct radiative impact by using volcanic index (calculated using clear‐sky net shortwave radiative flux at surface averaged over the selected domain) and introduced it as a predictor in multiple regression analysis; however, it gave similar qualitative responses (not shown) as is calculated using residual approach. The volcanic residual signal estimated here might contain some contributions (Fujiwara et al, ) from other random variations that are not included in the multiple regression; however, these contributions are much smaller compared to volcanic direct radiative and posteruption ENSO impacts, especially in the summer season (Dogar, Stenchikov, et al, ). Both the model and observation display cooling and drying anomaly over the entire MEA and South Asian regions except over the tropical belt that displays warming and drying anomaly.…”
Section: Resultsmentioning
confidence: 93%
“…Initially, we showed combined/total anomalous signal that contains both postvolcanic direct radiative and indirect dynamic circulation impacts, and afterward, we analyzed posteruption circulation impacts and volcanic direct radiative impacts separately that are computed using multiple regression technique (section ). Multiple regression technique has been widely used to separate the volcanic signal and other major variability modes (see, e.g., Randel, ; Fujiwara et al, ; Dogar & Sato, ; Gu & Adler, 2010; Gu & Adler, ). Nonetheless, some shortcomings of using regression are possible as the climate system is complex (Mitchell et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that stratospheric temperature is driven by radiative heating processes involving O 3 , CO 2 , and water vapor (Gettelmann et al, ), by the Brewer‐Dobson circulation (Butchart, ) and by external forcing such as the solar cycle or volcanic eruptions (Fujiwara et al, ; Mitchell et al, ; Vernier et al, ). The observed positive temperature trends in the lower stratosphere may be explained using a simple one‐dimensional radiative transfer model where energy transfer is determined primarily by three processes (Andrews et al, ; Gettelmann et al, ; London, ).…”
Section: Discussionmentioning
confidence: 99%
“…The JRA team has reported on stratospheric temperature issues with JRA-25 and discussed the cause of the biases (Onogi et al, 2007). Fujiwara et al (2015) explained that the radiative scheme used in the JRA-25 forecast model has a known cold bias in the stratosphere, and the TOVS SSU/MSU measurements do not have a sufficient number of channels to correct the model's cold bias; after introducing the ATOVS AMSU-A measurements in 1998, such a cold bias disappeared in the JRA-25 data product. However, with JRA-55 using a new radiation scheme in the forecast model, the stratospheric temperature during the TOVS period has been much improved.…”
Section: Evolution Of the Differences Among Reanalyses With Timementioning
confidence: 99%